Adaptation of Tropical Forage Grasses to Moderate Shade in Coal Mine Reclamation Systems - Purwokusumaning Daru, Taufan; Ardhani, Fikri; Mayulu, Hamdi; Ardiansyah, Ardiansyah; Fadillah, Muhammad Rizki; Maulida, Septiana (CV. Komunitas Dunia Peternakan, 2026)
Coal mining activities in East Kalimantan have significantly contributed to regional economic development, but they have also resulted in extensive land degradation that requires effective reclamation strategies. The integration of forage crops in reclaimed mine lands offers an opportunity to simultaneously support ecological restoration and livestock production. However, the performance of forage grasses under shaded conditions created by revegetation trees remains insufficiently understood. This study aimed to evaluate the physiological responses, morphological characteristics, and nutritional quality of two forage grass species, Brachiaria humidicola and Stenotaphrum secundatum, grown under shaded conditions on reclaimed coal mine land. The experiment was conducted at the PT Kitadin Embalut reclamation site, East Kalimantan, using a split-plot design with two shading levels (0% and 50%) as the main plots and two grass species as subplots. Each treatment was replicated six times. Variables measured included dry matter yield, leaf-to-stem ratio, chlorophyll content (a, b, and total), crude protein, and crude fiber content. The results showed that a 50% shading level significantly influenced physiological and morphological responses of the grasses. Stenotaphrum secundatum exhibited a marked increase in chlorophyll content under shaded conditions, indicating a stronger acclimation to low light environments compared with Brachiaria humidicola. Shading also reduced the leaf-to-stem ratio in both species. However, dry matter production was not significantly affected by shading, suggesting that both grasses were able to maintain biomass accumulation under moderate shade conditions. Shading slightly reduced crude protein and crude fiber contents.